Amino acid solutions on the growth of the ornamental plant Impatiens walleriana grown under root restriction stress - Hakim, Guido; Gandolfo, Esteban; Salinas, Máximo; Giardina, Ernesto; Di Benedetto, Adalberto (Ornamental Horticulture, 2022)
The use of amino acid solutions as bio-fertilizers was introduced in the food and ornamental plant industry about two decades ago. Sprays containing amino acids either alone or combined have been proven effective to increase plant growth. However, many of the new commercial solutions including amino acids as bio-fertilizers have no published data available on bedding plants. Thus, the aims of this study were to determine the changes in fresh weight accumulation in the bedding pot plant Impatiens walleriana and the physiological mechanism involved in plants sprayed with different amino acid solutions and to characterize the responses to root restrictions under nursery with non-limited nitrogen supply. The experiment was carried out inside a greenhouse in the campus of the Faculty of Agronomy of the University of Buenos Aires, Argentina. To reach the objectives, Impatiens walleriana ‘Xtreme White’ seeds were grown in 50-cell (55.7 cm3 cell-1) and 288-cell (6.18 cm3 cell-1) plug trays and then transplanted and grown at 3-L pots. Eleven solutions (100 mg L-1) containing an equal amount of each of the following amino acids: alanine, cysteine, aspartic acid, glutamic acid, glycine, leucine, lysine, methionine, threonine, tryptophan and valine, a control without amino acids, and a solution containing all amino acids (Mix) (9.1 mg L-1 of each amino acid) were sprayed when the first true leaf pair was developed. Our results showed that the different synthetic amino acids tested, alone or combined, had additive and antagonistic effects on the leaf area and fresh-dry weight in Impatiens walleriana plants.